Variability of Memory B cell Markers in a Cohort of Common Variable Immune Deficiency Patients over 6 months. (22nd May 2013) - Koopmans, W.; Woon, S.‐T.; Zeng, I. S. L.; Jordan, A.; Brothers, S.; Browett, P.; Ameratunga, R.
Abstract Common Variable Immunodeficiency Disorder (CVID) is a complex disorder that predisposes patients to recurrent and severe infections. Immunophenotypic classification schemes were developed to categorize patients with CVID into phenotypic and prognostic groups based on different memory B cell subsets. Whether the B cell subset analysis is stable over time has not been investigated. B cell phenotyping in patients with CVID (n = 15) and sex‐ and age‐matched controls (n = 26) were carried out according to the three B cell classifications. Patients with CVID were evaluated monthly over 6 months. Controls were assessed once during the study. We scored how often each patient was assigned to the same group within each classification. The Freiburg classification assigned patients to the same group at a rate of 73% and the Paris classification at 88%. The EUROclass classification of smB− versus smB+ was at 90%. The two subclassifications [(smB‐21low or smB‐21norm) and transitional B] were at 87% and 97%, respectively. The level of naïve B cells measured in all patients with CVID during the 6‐month evaluation was the most stable B cell subset. We conclude that all classifications systems show considerable variability, but the EUROclass classification was the most reliable scheme for our 15 CVID and 26 healthy cohorts. Our results indicate that phenotypic classifications within CVID will be difficult while there is variability of commonly used assays.